Paving the way to e-services: Innovation through online games - Giuditta De Prato; Jean Paul Simon (International Telecommunications Society (ITS), 2011)
The transformative power of organizational and service innovations on value or supply chains has been the object of several studies. The question identified in this paper is how disruptive trends in the videogames world can have spill-over effects in the broader realm of e-services. Section 1 opens with a brief review of literature. Section 2 proposes a description of the on-line games industrial ecosystem, the characteristics of the production process and the value chain in the online video games industry. The main techno-economic models for the production and distribution of online games are described in a third section with an emphasis on service creation, and illustrated by some case studies. The last part highlights the trend of innovative paths towards an economy of e-Services which are driven by the evolution of online games in a converged environment.
Keywords: 330; Online value creation; virtual world; virtual good; value chain; digital content convergence; new business models; services